PROMOTING INTERCULTURAL COMMUNICATION AND UNDERSTANDING IN DIVERSE LANGUAGE LEARNING ENVIRONMENTS - Wirentake, Wirentake (Transpublika Publisher, 2022)
As we move more and more towards a world that is globalized, it has become increasingly important for people in different cultures to communicate well together; this is particularly urgent in language classes. This research seeks to identify mechanisms through which students from various nations can interact in a way that fosters intercultural understanding. The study incorporates both qualitative data obtained from interviews and an analysis of relevant literature utilizing mixed methods research techniques. The major findings indicate that incorporating intercultural competence into language instruction can greatly enhance learner’s empathy, adaptability and cultural awareness. Such skills are vital while navigating multicultural interactions and ultimately help students become better world citizens. The study emphasizes the need to integrate intercultural communication training in language programs to create more inclusive and peaceful learning spaces.